2023
DOI: 10.1177/15347354221151021
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Peel Extract Sensitizes Hepatocellular Carcinoma Cells to Ionizing Radiation, Induces Apoptosis and Inhibits MAPK, JAK/STAT3, β-Catenin/NOTCH, and SOCS3 Signaling

Abstract: Tumor resistance is typically blamed for the failure of radiotherapy and chemotherapy to treat cancer in clinic patients. To improve the cytotoxicity of tumor cells using radiation in conjunction with specific tumor-selective cytotoxic drugs is crucial. Pomegranate has received overwhelmingly positive feedback as a highly nutritious food for enhancing health and treating a variety of ailments. In the present study, we aimed to examine the effects as well as mechanism of action of pomegranate peel extract (PPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…The cytotoxicity and IC50 results of this study on the HNO-97 with PPE treatment are in accordance with the results of colon carcinoma cell line HCT116 where the IC50 was about 74.84 µg/mg ( Keta et al, 2020 ) with the results of Elbakry et al in which liver cancer cell line HepG2 was 83.9 µg/mg ( Elbakry et al, 2023 ) and also with the POMx powder (capsules loaded pomegranate Juice powder),which was 80.53 µg/mg with Ca9-22 oral carcinoma cell line ( Peng et al, 2021 ). These results disagree with the results of melanoma (HTB140), large cell lung carcinoma (HTB177), and breast cancer (MCF7) ( Keta et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The cytotoxicity and IC50 results of this study on the HNO-97 with PPE treatment are in accordance with the results of colon carcinoma cell line HCT116 where the IC50 was about 74.84 µg/mg ( Keta et al, 2020 ) with the results of Elbakry et al in which liver cancer cell line HepG2 was 83.9 µg/mg ( Elbakry et al, 2023 ) and also with the POMx powder (capsules loaded pomegranate Juice powder),which was 80.53 µg/mg with Ca9-22 oral carcinoma cell line ( Peng et al, 2021 ). These results disagree with the results of melanoma (HTB140), large cell lung carcinoma (HTB177), and breast cancer (MCF7) ( Keta et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The flowcytometric analysis apoptosis assays significant results performed on HNO-97 with the PPE can be conducted to results of hepatocellular carcinoma HEPG2 cell line, Prostate cancer, and cervical cancer ( Deng et al, 2017 , Fazio et al, 2018 , Chaves et al, 2020 , Elbakry et al, 2023 ). These results can also be correlated to Peng et al who studies the effect of POMx, which showed an increasing apoptotic effect of OC (Ca9-22,HSC-3,and OC-2) ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 functions as a key modulator of several biological processes, including proliferation and apoptotic cell death, in various types of cancer. [13][14][15][16] In our previous study, we found that STAT3 phosphorylation was significantly higher in human OSCC tumors compared with that in the normal oral mucosa. 17 Therefore, we determined whether genipin can suppress STAT3 phosphorylation in human OSCC.…”
Section: Genipin Suppresses Stat3 Phosphorylation and Its Nuclear Loc...mentioning
confidence: 89%
“…However, recent research has shown that it contains a wealth of bioactive phytochemicals. These compounds can potentially act as antioxidants, physiological agents, antimicrobial agents, and immune system stimulants (Elbakry et al, 2023 ; Smaoui et al, 2019 ). Extracts from the peel have been traditionally used to treat diseases such as type 2 diabetes and carcinoma (Teniente et al, 2023 ; Zare et al, 2023 ).…”
Section: Chemical Composition Of Pomegranatesmentioning
confidence: 99%
“…Punica granatum (pomegranate) has attracted the attention of researchers due to its potential for the use in medicine and in the food industry. The beneficial compounds found in pomegranates are not only present in the edible part of the fruit but also in non-edible parts such as leaves, buds, bark, seeds, peel, and blossoms (Elbakry et al, 2023;Xiang et al, 2022). Pomegranate supplementation has been demonstrated in multiple studies to have neuroprotective (George et al, 2022), anti-inflammatory (Sayed et al, 2022), hepatoprotective (Al-Gareeb & Mohammed, 2022;Diab et al, 2022), and antioxidant effects (Lotfi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%